2022
DOI: 10.1021/acsanm.1c03838
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Nanoscale ZnO Tetrapod-Based Transducers for Tetracycline Detection

Abstract: Antibiotic pollution of freshwaters and even food products has become an important concern worldwide. Hence, it is of utmost importance to develop cost-effective and reliable devices that can provide information on the presence of such contaminants to the general population. In the present work, zinc oxide (ZnO) nanotetrapods (NTP) produced via a high yield laser processing approach were used as transducers in a luminescent-based immunosensor to detect tetracycline (TC). These tetrapodal structures present nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 69 publications
5
11
0
Order By: Relevance
“…Higher TC concentrations were tested (up to 500 µg L −1 ), however, the signal was seen to reach a plateau in the high concentration regime (above ~10 µg L −1 ), which suggests that the majority of the antigenbinding sites were already engaged with TC antigens at such concentrations. Indeed, TC concentrations usually found in freshwaters are in the range of 0.008-1 µg L −1 [108], which is in agreement with the one obtained for our sensors [107]. A LOD of ~1.2 ng L −1 was estimated in this case, corresponding to one of the lowest LOD values reported so far for TC.…”
Section: Immunosensorssupporting
confidence: 91%
See 4 more Smart Citations
“…Higher TC concentrations were tested (up to 500 µg L −1 ), however, the signal was seen to reach a plateau in the high concentration regime (above ~10 µg L −1 ), which suggests that the majority of the antigenbinding sites were already engaged with TC antigens at such concentrations. Indeed, TC concentrations usually found in freshwaters are in the range of 0.008-1 µg L −1 [108], which is in agreement with the one obtained for our sensors [107]. A LOD of ~1.2 ng L −1 was estimated in this case, corresponding to one of the lowest LOD values reported so far for TC.…”
Section: Immunosensorssupporting
confidence: 91%
“…where I UV 0 stands for the integrated intensity of the NBE for the blank/reference (without any analyte) and I UV Analyte corresponds to the integrated intensity of the same emission after analyte immobilization for each concentration C [9,107]. Therefore, the data demonstrated that the developed biosensor can be employed in hCG quantification, presenting fairly results in the range between 5 and 50 ng mL −1 [9].…”
Section: Immunosensorsmentioning
confidence: 76%
See 3 more Smart Citations